Black textile with bottom metallized surface having enhanced radiative cooling under solar irradiation. (April 2021) - Kim, Gunwoo; Park, Kyuin; Hwang, Kyungjun; Choi, Chulmin; Zheng, Zengwei; Seydel, Roland; Coza, Aurel; Jin, Sungho
Abstract: The cooling performance of garments can play an important role of enabling comfortable human activities under extreme environments. Imparting extra cooling performance to a garment in a passive way is extremely challenging under the sunlight which provides a huge energy influx to the garment, especially made of black colored textile. In this study, a solar-adaptive-textile (SAT) has been designed and experimentally demonstrated. Near-infrared (NIR) transmittance to the human skin from the solar irradiance has been intercepted by incorporating a nanoscale sputtered thin aluminum metal film underneath the textile layer facing the skin. The high-pressure sputtering employed allows a deep penetration of aluminum into the fabric structure for enhanced solar-energy-blocking effect and film stability. The aluminum layer effectively reduces the solar irradiance as well as the thermal radiation from the textile, which gets heated in lieu of the human skin. The outdoor, under-the-sun measurements with a simulated skin showed an outstanding 2 ℃ cooling effect compared to the normal textile without the metal film, while preserving most of the given textile properties such as colors, air permeability and wicking behavior. Graphical Abstract: ga1 Highlights: Nano Al film underneath textile can block NIR transmittance from solar irradiance. Emissivity of heated textile is blocked by Al film. The simulated skin showed 2 ℃ cooling performance with nano Al filmed textile. Al film layer on textile showed a robust adhesion which endures real-life abrasion.